KEMAMPUAN TUMBUH STEK PUCUK NYAMPLUNG MENGGUNAKAN TRUBUSAN DARI ANAKAN DAN POHON INDUK - Tri Maria Hasnah; Eritrina Windyarini; Hamdan Adma Adinugraha (Jurnal Pemuliaan Tanaman Hutan, 2019)
The tree improvement research of nyamplung has entered the selection stage at the individual levels having high quality and oil yield properties. In order to maintain the superiority of this characteristics, a proper vegetative propagation techniques is required to multiply selected trees.The purpose of this study is to determine the effect  of cutting materials from sprouts on seedlings and mother trees. The study was arranged in a completely randomized design with factorial pattern. The factors tested were cutting materials (namely sprouts on seedlings and on the mother tree branches) and application of growth hormone types (control, pasta and  powder). The results showed that the survival rates and the growth of cuttings from seedlings and mother trees  were relatively similar. However, the rooting percentages and the growth of cuttings were significantlyinfluenced by the interaction between the two factors. The survival rates of shoot cuttings varied from 51.92 to 82.30% and rooting percentages range from 32 to 70%. The best result of rooting percentage and shoot cuttings growth were obtained at shoot cuttings from seedlings with growth hormone in the pasta type.